Early Pregnancy Diabetes Screening and Diagnosis: Prevalence, Rates of Abnormal Test Results, and Associated Factors. Issue 5 (November 2017) - Mission, John F.; Catov, Janet; Deihl, Tiffany E.; Feghali, Maisa; Scifres, Christina
Abstract : OBJECTIVE: To evaluate the prevalence of early diabetes screening in pregnancy, rates of abnormal diabetes test results before 24 weeks of gestation, and factors associated with early diabetes screening. METHODS: This was a retrospective cohort study of all singleton deliveries from 2012 to 2014 among diverse clinical practices at a large academic medical center. We assessed rates of early (less than 24 weeks of gestation) and routine (at or beyond 24 weeks of gestation) diabetes screening, with abnormal test results defined using the Carpenter-Coustan criteria, a 50-g glucose challenge test result greater than 200 mg/dL, or a hemoglobin A1C level greater than 6.5%. Univariate and multivariate analyses were used to evaluate clinical and demographic determinants of screening and diagnosis. RESULTS: Overall, 1, 420 of 11, 331 (12.5%) women underwent early screening. Increasing body mass index (BMI) category, race, public insurance, history of gestational diabetes mellitus, a family history of diabetes, and chronic hypertension were associated with early screening. Early screening rates rose with increasing BMI category, but only 268 of 551 (48.6%) of women with class III obesity underwent early screening. Among those screened early, 2.0% of normal-weight women, 4.0% of overweight women, 4.2% of class I obese women, 3.8% of class II obese women, and 9.0% of class III obese women had abnormal early test results ( P <.001). CONCLUSION: Early diabetes screening is used inconsistently, and many women with risk factors do not undergo early screening. A significant proportion of women with class III obesity will test positive for gestational diabetes mellitus before 24 weeks of gestation, and studies are urgently needed to assess the effect of early diabetes screening and diagnosis on perinatal outcomes in high-risk women. Abstract : Many candidates for early pregnancy diabetes screening go untested.